Design Guidelines for Smart Nursing Homes in the Context of Aging - Xiao Teng; Zhenjiang Shen; Yuntian Zhang (Buildings)
With global aging accelerating, improving the efficiency and quality of elderly care is increasingly critical. This study proposes smart nursing home design guidelines to enhance care through smart device integration. The guidelines include two parts: smart device selection criteria, based on next-generation elderly needs identified via Japanese public surveys, and smart nursing home model templates, built upon existing Japanese housing standards. These guidelines provide practical recommendations on device usage, placement, and spatial optimization to improve accessibility and nursing efficiency. The study concludes by validating the effectiveness of the guidelines in addressing the requirements of the next generation of elderly people through a case study, which shows that although construction costs have increased by an average of 18.35%, the guidelines have ensured a safer, more comfortable, and technologically advanced nursing home environment.